2023
DOI: 10.3989/revmetalm.253
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on microstructure, hardness and tribological behaviour of AA7075-Al2O3 composites synthesized via stir casting route

Mathusoothana Perumal Ezhilan,
Loganathan Emmanual,
Sivasamy Alagarsamy
et al.

Abstract: Aluminium matrix composite (AMC) materials play an important role in the field of automobile and aerospace industries due to their excellent properties. In this research, aluminium alloy (AA7075) was reinforced with alumina (Al2O3) particles to improve their hardness and tribological behaviour of the base alloy. Four composites were prepared by varying the content (4, 8 and 12 wt.%) of Al2O3 particles through the stir casting technique. The surface morphology of the proposed composites ensured the uniform dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Their research demonstrated that the wear resistance of the composites was significantly higher than that of the aluminum alloy, and this wear resistance further increased with higher content of Al 2 O 3 particles. It is noteworthy to mention that reduction in wear resistance of Al/Al 2 O 3 composites, compared to the alloy matrix, has been reported in some studies where an excessive amount of reinforcement has been added to the composite [38,74]. This leads to agglomeration and the formation of porosities in the microstructure, underscoring the importance of achieving uniform distribution of reinforcements and homogeneity of the composite in tribological properties.…”
Section: Ceramic Reinforcementsmentioning
confidence: 97%
“…Their research demonstrated that the wear resistance of the composites was significantly higher than that of the aluminum alloy, and this wear resistance further increased with higher content of Al 2 O 3 particles. It is noteworthy to mention that reduction in wear resistance of Al/Al 2 O 3 composites, compared to the alloy matrix, has been reported in some studies where an excessive amount of reinforcement has been added to the composite [38,74]. This leads to agglomeration and the formation of porosities in the microstructure, underscoring the importance of achieving uniform distribution of reinforcements and homogeneity of the composite in tribological properties.…”
Section: Ceramic Reinforcementsmentioning
confidence: 97%